Does it pay to be eco? The mediating role of competitive benefits and the effect of ISO14001. Issue 5 (October 2017) - Hojnik, Jana; Ruzzier, Mitja
Abstract: Eco-innovation has become an important instrument to help companies reduce their environmental impact and gain a competitive advantage in increasingly competitive environments. Despite recent research conducted in this field, findings concerning the relationship between eco-innovation and firm performance remain conflicting, inconclusive and incomplete. This study aimed to clarify this relationship by incorporating competitive benefits as a mediator between eco-innovation and firm performance. Three core questions are examined: How does eco-innovation influence competitive benefits and firm performance? Do competitive benefits mediate the relationship between eco-innovation and firm performance? How does ISO14001 influence competitive benefits and firm performance? The study finds that competitive benefits mediate and strengthen the relationship between eco-innovation and firm performance. In addition, the results reveal that ISO14001 positively affects competitive benefits and thus leads to greater competitive benefits, while the association between ISO14001 and firm performance is not found to be statistically significant. The paper concludes with a discussion of implications for policy makers and companies, limitations, and future research directions. Highlights: Adoption of eco-innovation (EI) leads to greater competitive benefits. EI positively and significantly affects firm performance. Competitive benefits mediate the relationship between EI and firm performance. ISO14001 exerts a positive effect on competitive benefits. The aforementioned relationships are tested and valid for different types of EI.